2014
DOI: 10.1016/j.jtcvs.2014.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Extubating in the operating room after adult cardiac surgery safely improves outcomes and lowers costs

Abstract: After cardiac surgery, OR extubation is safe and might provide improvement in length of stay and cost compared with early postoperative ICU extubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 27 publications
0
57
0
5
Order By: Relevance
“…Badhwar et al 7 examined the outcomes and compared the costs of extubation in the operating room vs early extubation in the ICU after elective open cardiac surgery. They found that extubation in the operating room resulted in a >20% cost reduction for the entire hospital stay compared with early extubation in the ICU with no effect on the reintubation rate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Badhwar et al 7 examined the outcomes and compared the costs of extubation in the operating room vs early extubation in the ICU after elective open cardiac surgery. They found that extubation in the operating room resulted in a >20% cost reduction for the entire hospital stay compared with early extubation in the ICU with no effect on the reintubation rate.…”
Section: Discussionmentioning
confidence: 99%
“…They found that extubation in the operating room resulted in a >20% cost reduction for the entire hospital stay compared with early extubation in the ICU with no effect on the reintubation rate. 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 There is evidence to suggest that extubation within the operating room (OR) itself may additionally reduce hospital LOS and costs without increasing major adverse event (MAE) rates or the need for reintubation. 15,16 Although there is an established association between prolonged mechanical ventilation and delirium, the nature of this association in the cardiac surgery patient is uncertain. 2 Evidence suggests that mechanical ventilation may be an independent risk factor for developing delirium; however, there are likely patient-specific and procedure-related factors confounding both the decision to extubate and the occurrence of postoperative delirium.…”
Section: Perspectivementioning
confidence: 99%